"Allow natural death" versus "do not resuscitate": three words that can change a life. Issue 1 (21st December 2007) - Venneman, S S; Narnor-Harris, P; Perish, M; Hamilton, M
Abstract : Physician-written "do not resuscitate" DNR orders elicit negative reactions from stakeholders that may decrease appropriate end-of-life care. The semantic significance of the phrase has led to a proposed replacement of DNR with "allow natural death" (AND). Prior to this investigation, no scientific papers address the impact of such a change. Our results support this proposition due to increased likelihood of endorsement with the term AND.